A green polyol approach for the synthesis of Cu2O NPs adhered on graphene oxide: a robust and efficient catalyst for 1, 2, 4-triazole and imidazo[1, 2-a]pyridine synthesis. (8th April 2022) - Kujur, Shelly; Verma, Shruti; Kumar, Akash; Sharma, Richa; Pathak, Devendra Deo
Abstract : Cu2 O NPs immobilized on graphene oxide are used as a heterogeneous catalyst for the synthesis of a series of 1, 2, 4-triazoles and imidazo[1, 2- a ]pyridines under solvent-free conditions. Abstract : A green "polyol method" is reported for the synthesis of Cu2 O nanoparticles (NPs) immobilized on graphene oxide (Cu2 O-GO), for the first time. The composition of the synthesised composite was characterized by FT-IR, Raman, PXRD, FESEM, high-resolution TEM, XPS, TGA and ICP-MS analysis. Its catalytic application, as a novel heterogeneous catalyst, has been investigated in the solvent-free synthesis of a series of pharmaceutically important heterocycles containing nitrogen, viz. 1, 2, 4-triazoles and imidazo[1, 2- a ]pyridines. The composite shows an extensive substrate scope and broad functional group resilience. This green methodology involves the use of inexpensive reactants, moderate temperature, and solvent-free conditions and affords an excellent yield of products. The composite is retrieved from reaction mixtures by filtration and can be reused up to five cycles without any noticeable loss in its catalytic activity for both reactions.